A Rare Form of Heteropagus Twinning: Three-Armed Infant with Spinal Dysraphism - Aynur Solak; Sonnaz Ergün; İpek Polat; Neslın Şahin; Berhan Genç (Case Reports in Pediatrics)
An ectopic or accessory limb attached to the back is an extremely rare and strange condition, and there are only a few documented cases in the worldwide literature. The first case was described by Jones and Larkin (1889). There are several theories regarding the origin of this condition. Asymmetric conjoined twinning which is located dorsally in the vertebral column (rachipagus) is the most probable diagnosis of our patient. Conjoined twinning is very rare and the incidence is 1 per 50 000 live births. Rachipagus is even rarer, with no more than 30 case reports so far (Chadha et al. (1993, 2006)). In this report, we present a patient who underwent successful surgical excision of a third arm attached to the back in the midline over the low-dorsal region. Differential diagnoses including teratoma and fetus in fetu are discussed.